High energy density molten lithium-sulfur and lithium-selenium batteries with solid electrolytes.

Molten lithium-sulfur and lithium-selenium batteries with a solid LLZTO electrolyte address the limitations of current Li-ion and Li-S/Li-Se batteries by providing high energy density, fast charging, and stability, suitable for advanced energy storage applications.

JP7600481B2Active Publication Date: 2024-12-17METAGENESIS LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021537134
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-28
Filing Date
2019-12-13
Publication Date
2024-12-17
Estimated Expiration
2039-12-13

AI Technical Summary

Technical Problem

Current lithium-ion batteries have a lower energy density, which limits their application in high-demand fields such as consumer electronics, aviation, and large-scale stationary storage, and existing Li-S and Li-Se batteries face issues like poor cycling stability, safety concerns, and lithium anode dendrites due to liquid organic electrolytes.

Method used

Development of molten lithium-sulfur and lithium-selenium batteries using a solid electrolyte composed of LLZTO, which includes a molten Li anode, molten S or Se cathode, and a solid electrolyte capable of conducting lithium ions, operating at elevated temperatures to facilitate rapid ion transport and prevent leakage.

Benefits of technology

The batteries achieve high energy density, fast charging and discharging rates, high coulombic efficiency, and stability, making them suitable for high-energy, high-power, long-life, and safe energy storage systems with potential for low cost and scalability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600481000001
    Figure 0007600481000001
  • Figure 0007600481000002
    Figure 0007600481000002
  • Figure 0007600481000003
    Figure 0007600481000003
Patent Text Reader

Abstract

Molten lithium-sulfur and lithium-selenium electrochemical cells are disclosed. A solid electrolyte separates the molten lithium metal or lithium metal alloy from the molten sulfur or molten selenium. The molten lithium-sulfur and lithium-selenium cells have low overpotentials, no side reactions, and no dendritic growth. These cells have high coulombic and energy efficiencies, thus offering a new chemistry for building high-energy, high-power, long-life, low-cost, and safe energy storage systems.
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] High energy density batteries are important for applications in consumer electronics, aviation, electric vehicles, and emerging large-scale stationary storage. Current state-of-the-art lithium-ion batteries (LIBs) have a capacity of 300Wh kg -1 Lower, 750Wh L -1 It has a lower energy density: 500Wh kg -1 Higher, 1000Wh L -1 Reliable battery systems with higher energy densities have yet to be developed to meet long-term demand. The energy density of Li-ion batteries is comparable to that of commercially available metal oxide cathodes (~140 mAh g -1 lithium iron phosphate) and commercially available carbon-based anodes (~340mAh g -1 The lithium storage capacity of lithium-ion batteries is limited by their inherent lithium-ion capacity (e.g., graphite in lithium-ion batteries) and by the traditional "sandwich" battery configuration (stacked current collector / cathode / separator / anode / current collector).

[0002] Improved batteries for power storage are desirable. Summary of the Invention

[0003] The present disclosure describes, in some embodiments, high energy density molten lithium-sulfur (Li-S) and lithium-selenium (Li-Se) batteries, which include, for example, a molten S or Se (or mixture) cathode, a molten Li anode, and a Li anode capable of conducting lithium ions. 6.4 La3Zr 1.4 Ta 0.6 O 12 The molten Li-S and Li-Se batteries can be prepared by incorporating a solid electrolyte consisting of (LLZTO). As shown in the experimental examples, such molten Li-S and Li-Se batteries exhibit excellent electrochemical performance, including high energy density, fast charge and discharge rates with high stability, high coulombic efficiency, and high energy efficiency.

[0004] As described herein in various embodiments, these solid electrolyte based molten Li-S and Li-Se batteries provide a new chemistry for building high energy, high power, long life, low cost, and safe energy storage systems. Such batteries can provide up to 2395 Wh kg -1 and 1015Wh kg -1 It is theoretically possible to reach an energy density of

[0005] According to one embodiment of the present disclosure, there is provided an electrochemical cell comprising an anode comprising lithium metal or a lithium alloy, a cathode comprising sulfur, selenium, or a mixture thereof, and a solid electrolyte positioned between the anode and the cathode, hi some embodiments, the solid electrolyte is capable of conducting lithium ions.

[0006] In various embodiments, at the operating temperature (e.g., 240° C.), the lithium metal or lithium alloy is molten, the sulfur or selenium is molten, and the solid electrolyte remains solid. In some embodiments, the electrochemical cell is configured to operate at a temperature ranging from 120° C. to 600° C.

[0007] The solid electrolyte may be prepared using a lithium ion conducting oxide, a lithium ion conducting phosphate, a lithium ion conducting sulfide, or a combination thereof. The lithium ion conducting oxide may be a garnet type oxide, a lithium superionic conductor (LISICON) type oxide, a perovskite type oxide, or a combination thereof.

[0008] Non-limiting examples of garnet-type oxides include Li 7-x La3Zr 2-x Ta x O 12 Tantalum-doped Li7La3Zr2O 12 where x is between 0.1 and 1.0. In some embodiments, x is between 0.4 and 0.6. Tantalum-doped Li7La3Zr2O 12 A specific example of this is Li 6.4La3Ta 0.6 Zr 1.4 O 12 , Li 6.5 La3Ta 0.5 Zr 1.5 O 12 , or Li 6.6 La3Ta 0.4 Zr 1.6 O 12 Includes.

[0009] The electrochemical cell may further include a cathode current collector in electrical communication with the cathode and an anode current collector in electrical communication with the anode. Both the anode current collector and the cathode current collector may be made of stainless steel.

[0010] In some embodiments, the cathode may be doped with a carbon conductive additive, hi some embodiments, sulfur or selenium and carbon are mixed in a molar ratio (m(S or Se):m(C)) of 3:1 to 20:1.

[0011] Various other embodiments also provide a power module including one or more of the electrochemical cells of the present disclosure, and the power module may further optionally include a heat source configured to heat the one or more electrochemical cells within the module. In an embodiment of the present invention, for example, the following items are provided: (Item 1) an anode comprising lithium metal or a lithium alloy; a cathode comprising sulfur, selenium or a mixture thereof; a solid electrolyte positioned between the anode and the cathode, the solid electrolyte being capable of conducting lithium ions; An electrochemical battery comprising: (Item 2) 2. The electrochemical cell of claim 1, wherein at operating temperatures, the lithium metal or lithium alloy is molten, the sulfur or selenium is molten, and the solid electrolyte remains solid. (Item 3) 2. The electrochemical cell of claim 1, wherein the solid electrolyte comprises a lithium ion conducting oxide, a lithium ion conducting phosphate, a lithium ion conducting sulfide, or a combination thereof. (Item 4) 4. The electrochemical cell of claim 3, wherein the solid electrolyte comprises a lithium ion conducting oxide. (Item 5) Item 5. The electrochemical cell of item 4, wherein the lithium ion conducting oxide comprises a garnet type oxide, a lithium superionic conductor (LISICON) type oxide, a perovskite type oxide, or a combination thereof. (Item 6) 5. The electrochemical cell of claim 4, wherein the lithium ion conducting oxide comprises a garnet-type oxide. (Item 7) The garnet-type oxide is a tantalum-doped Li 7 La 3 Zr 2 O 12 7. The electrochemical cell of claim 6, comprising: (Item 8) The garnet-type oxide is Li 7-x La 3 Zr 2-x Ta x O 12 7. The electrochemical cell of claim 6, comprising: (Item 9) The garnet-type oxide is Li 7-x La 3 Zr 2-x Ta x O 12 7. The electrochemical cell of claim 6, comprising: (Item 10) The garnet-type oxide is Li 6.4 La 3 Ta 0.6 Zr 1.4 O 12 , Li 6.5 La 3 Ta 0.5 Zr 1.5 O 12 , or Li 6.6 La 3 Ta 0.4 Zr 1.6 O 12 7. The electrochemical cell of claim 6, comprising: (Item 11) 11. The electrochemical cell of any one of the preceding claims, further comprising a cathode current collector in electrical communication with the cathode. (Item 12) 12. The electrochemical cell of claim 11, wherein the cathode current collector comprises stainless steel. (Item 13) 12. The electrochemical cell of claim 11, further comprising an anode current collector in electrical communication with the anode. (Item 14) Item 14. The electrochemical cell of item 13, wherein the anode current collector comprises stainless steel. (Item 15) Item 12. The electrochemical cell of item 11, wherein the solid electrolyte is in the form of a tube and the cathode is disposed within the tube. (Item 16) 12. The electrochemical cell of claim 11, wherein the solid electrolyte has a relative density of 95% to 99.9%. (Item 17) Item 16. The electrochemical cell of item 15, wherein the cathode current collector is in the form of a cylinder external to the tube, and the cathode is disposed between the tube and the cylinder. (Item 18) Item 12. The electrochemical cell of item 11, further comprising a seal configured to hold the anode and the cathode. (Item 19) Item 19. The electrochemical cell of any one of items 1 to 18, wherein the electrochemical cell is configured to operate at a temperature in the range of 120° C. to 600° C. (Item 20) 20. The electrochemical cell of any one of the preceding claims, wherein the cathode further comprises a carbon conductive additive. (Item 21) 21. The electrochemical cell of item 20, wherein the sulfur or selenium and carbon are mixed in a molar ratio (m(S or Se):m(C)) of 3:1 to 20:1. (Item 22) 22. A power module comprising one or more of the electrochemical cells according to any one of the preceding claims. (Item 23) Item 23. The power module of item 22, further comprising a heat source configured to heat the one or more of the electrochemical cells. [Brief description of the drawings]

[0012] The drawings described herein are for illustration purposes only and are not intended to limit the scope of the present disclosure.

[0013] [Figure 1] FIG. 1 illustrates a cross-sectional view of an example lithium || solid electrolyte || S or Se electrochemical cell provided by the present disclosure.

[0014] [Figure 2a] 1 shows the structure and energy density of molten Li-S and Li-Se batteries. [Figure 2b] 1 shows the structure and energy density of molten Li-S and Li-Se batteries. [Figure 2c]1 shows the structure and energy density of molten Li-S and Li-Se batteries. [Figure 2d] The structure and energy density of molten Li-S and Li-Se batteries are shown. a shows a schematic of molten Li-S and Li-Se batteries. The inset shows the cross-section of the battery. b shows a comparison of the energy densities of the different batteries. c and d show the calculations of the gravimetric and volumetric energy of molten Li-S and Li-Se batteries, where the energy calculations are based on the volume and mass of the lithium anode, S or Se cathode, conductive additive, and LLZTO tube. In our calculations, the wall thickness of the LLZTO tube was set to 1.5 mm, and the densities of the LLZTO tube and stainless steel case were set to 5 g cm-3 and 8 g cm-3.

[0015] [Figure 3a] Electrochemical performance of a molten Li-S battery operating at 240 °C is shown. [Figure 3b] Electrochemical performance of a molten Li-S battery operating at 240 °C is shown. [Figure 3c] Electrochemical performance of a molten Li-S battery operating at 240 °C is shown. [Figure 3d] Figure 1 shows the electrochemical performance of a molten Li-S battery operating at 240°C. a) Voltage profile during charge-discharge cycling for the 1st to 5th cycles at 10 mA cm-2. b) Coulombic efficiency, energy efficiency, and specific capacity as a function of cycle number. c) Representative voltage profile during the 20th, 30th, and 40th charge-discharge cycles. d) C-rate performance of a molten Li-S battery.

[0016] [Figure 4a] Electrochemical performance of a molten Li-Se battery operating at 240 °C is shown. [Figure 4b] Electrochemical performance of a molten Li-Se battery operating at 240 °C is shown. [Figure 4c] Electrochemical performance of a molten Li-Se battery operating at 240 °C is shown. [Figure 4d] Electrochemical performance of a molten Li-Se battery operating at 240 °C is shown. [Figure 4e] Electrochemical performance of a molten Li-Se battery operating at 240 °C is shown. [Figure 4f] Figure 1 shows the electrochemical performance of a molten Li-Se cell operating at 240°C. a) Voltage profile during charge-discharge cycles for the 1st to 5th cycling at 30 mA cm-2. b) Coulombic efficiency, energy efficiency, and specific capacity as a function of cycle number. c) Representative voltage profiles during the 50th, 100th, and 300th charge-discharge cycles. d) C-rate performance of a molten Li-Se cell. e) Representative voltage profiles at different C-rates (0.5C-3C). f) Coulombic efficiency, energy efficiency, and specific capacity as a function of cycle number at 3C.

[0017] [Figure 5a] The electrochemical performance of a molten Li-Se battery operating at 300 °C is shown. [Figure 5b] The electrochemical performance of a molten Li-Se battery operating at 300 °C is shown. [Figure 5c] The electrochemical performance of a molten Li-Se battery operating at 300 °C is shown. [Figure 5d] The electrochemical performance of a molten Li-Se battery operating at 300 °C is shown. [Figure 5e] Electrochemical performance of a molten Li-Se battery operating at 300°C. a) Electric vehicle fast charge mode enabled by adjusting operating temperature. b) Variation in coulombic efficiency, energy efficiency, and specific capacity as operating temperature increases from 240°C to 300°C at 4C. c) Coulombic efficiency, energy efficiency, and specific capacity as a function of cycle number at 4C. d) C-rate performance of a molten Li-Se battery. e) Coulombic efficiency, energy efficiency, and specific capacity as a function of cycle number at 10C.

[0018] [Figure 6] a and b show the phase diagrams of Li-S (a) and Li-Se (b).

[0019] [Figure 7] XRD measurements of LLZTO electrolyte tubes after immersion in molten lithium at 300 °C for 2 months are shown. Peaks at theoretical positions from the LLZTO structure are indexed. It can be seen that both XRD patterns (before and after immersion in molten lithium for 2 months) match well with the standard pattern known for the cubic garnet phase Li5La3Nb2O12 (PDF45-0109).

[0020] [Figure 8] The ionic conductivity of LLZTO pellets at temperatures from 20°C to 300°C is shown.

[0021] [Figure 9] a to d show SEM images of the surface (a, b, c) and cross-section (d) of a LLZTO electrolyte tube.

[0022] [Figure 10] a and b show the schematic (a) and result (b) of the impermeability test of the LLZTO electrolyte sheet. ×: the LLZTO sheet is ruptured and the flow rate is outside the range of the gas flow meter. The gas pressure difference (P1-P0) on the two sides of the ceramic electrolyte is gradually increased until the electrolyte is ruptured. The gas flow rate on the ambient air side and the maximum pressure difference that the ceramic electrolyte can withstand were recorded. The thickness of the LLZTO electrolyte sheet: 200 μm, and the diameter of the test chamber d = 12.0 mm.

[0023] [Figure 11] Comparison of the vapor pressure of Se and S at different temperatures. The vapor pressure was calculated based on the Antoine equation.

[0024] [Figure 12]The results of the volatilization experiment of Se and S are shown. 1g of Se and 1g of S were placed in separate open glass containers and heated at 300°C in a full argon atmosphere in an oven. Their weights were measured every hour.

[0025] [Figure 13] The results of freeze / thaw tests of a molten Li-Se battery from 240° C. to 20° C. during discharge / charge are shown. The molten Li-Se battery was stopped from heating (naturally cooled down to 20° C.), left at 20° C. for 25 minutes during the charge and discharge process, and then returned to 240° C. again.

[0026] [Figure 14] Figures a and b show the results of a self-discharge experiment of a molten Li-Se battery at an operating temperature of 300 °C with a current density of about 10 mA cm-2. The cell was fully charged to 2.3 V and then stopped at 300 °C for 10 days (240 h) before being discharged again.

[0027] [Figure 15] 1 shows a geometric model of a molten Li-S or Li-Se battery.

[0028] [Figure 16] FIG. 16 shows a cross-sectional view of the molten Li—S or Li—Se battery of FIG.

[0029] Detailed reference will now be made to certain embodiments of the present disclosure. Although specific embodiments of the present disclosure have been described, it will be understood that it is not intended to limit the embodiments of the present disclosure to the disclosed embodiments. On the contrary, reference to the embodiments of the present disclosure is intended to encompass alternatives, modifications, and equivalents that may be included within the spirit and scope of the embodiments of the present disclosure as defined by the appended claims. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] For the purposes of the following description, it is understood that the embodiments provided by the present disclosure may assume various alternative variations and step sequences, unless expressly specified to the contrary. Moreover, other than in the examples or where otherwise indicated, for example, all numbers expressing the amounts of ingredients used in the specification and claims are understood to be modified in all instances by the term "about". Thus, unless otherwise indicated, the numerical parameters set forth in the following specification and the appended claims are approximations that may vary depending on the desired properties to be obtained. At the very least, there is no attempt to limit the application of the doctrine of equivalents to the scope of the claims, and each numerical parameter should at least be construed in light of the number of significant digits recited and by applying ordinary rounding techniques.

[0031] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible, however, any numerical values ​​inherently contain certain errors necessarily resulting from normal variations found in their respective testing measurements.

[0032] It should also be understood that any numerical range described herein is intended to include all subranges subsumed therein. For example, a range of "1 to 10" is intended to include all subranges between the recited minimum of about 1 and the recited maximum of about 10, inclusive, i.e., having a minimum value equal to or greater than about 1 and a maximum value equal to or less than about 10. Also, in this application, the use of "or" means "and / or" unless specifically stated otherwise, even though "and / or" may be expressly used in certain instances.

[0033] Electrochemical cells refer to devices that store and generate electrical energy, including batteries. The electrochemical cells provided by the present disclosure may be rechargeable.

[0034] Since the discovery of sulfur (S) and selenium (Se) as electrodes in batteries, most of the research on Li-S and Li-Se batteries has focused on battery structures with solid-state Li, solid-state S or Se (powder or different S / C or Se / C composites), and liquid organic electrolyte. However, these battery structures inevitably encounter intrinsic problems, including 1) poor cycling stability and low coulombic efficiency, 2) safety issues resulting from the high flammability of liquid organic electrolyte, and 3) dendritic growth of lithium anode and its side reactions in electrolyte. In addition, the large volume change of solid S and Se during charging and discharging will cause active S or Se to detach from the current collector, thus aggravating the cycling instability and reducing the utilization of Se and S. These problems have seriously hindered the industrialization of Li-S and Li-Se batteries.

[0035] These and other challenges have been readily overcome in the present technology. Described herein are high energy density molten lithium-sulfur (Li-S) and lithium-selenium (Li-Se) batteries that include, for example, a molten S or Se (or mixture) cathode, a molten Li anode, and a solid electrolyte capable of conducting lithium ions (e.g., Li 6.4 La3Zr 1.4 Ta 0.6 O 12 As shown in the experimental examples, such molten Li-S and Li-Se batteries exhibit excellent electrochemical performance, including (1) high energy density, (2) fast charge and discharge rates with high stability, and (3) high coulombic efficiency and high energy efficiency.

[0036] In terms of energy density, the tested batteries have a maximum energy density of 880Wh kg for Li-S batteries. -1 or 1400Wh L -1 , 530Wh kg for Li-Se battery -1 and 1250Wh L -1The energy density was calculated based on the weight and volume of all battery materials, including the anode, cathode, solid electrolyte, and conductive additives (except the stainless steel can). For the charge / discharge speed, take the Li-Se battery as an example: 300 °C, 100 mA cm -2 and a current density of 180 mW cm -2 At a power density of 10 ...

[0037] According to one embodiment of the present disclosure, there is provided an electrochemical cell comprising an anode comprising lithium metal or a lithium alloy, a cathode comprising sulfur or selenium, and a solid electrolyte positioned between the anode and the cathode, the solid electrolyte capable of conducting lithium ions.

[0038] A schematic of an example of an electrochemical cell, such as a battery provided by the present disclosure, is shown in Figure 1. The battery comprises an anode 102 comprising lithium metal or a lithium metal alloy, a cathode 104 comprising sulfur or selenium, and a solid electrolyte 103 in the form of a tube adjacent to and separating the anode 102 from the cathode 104. In addition, the battery may include an anode current collector 105 in contact with the anode 102 and in electrical communication with a negative electrode 106. The cathode 104 is electrically connected to and surrounded by a cylinder 101, which also functions as a cathode current collector and positive electrode.

[0039] The solid electrolyte may be in the form of an open-ended cylinder or a cylinder with one of the ends closed. One or both open ends of the cylinder may be sealed with a material capable of maintaining the integrity of the seal under operating conditions such as temperatures below 600° C., during temperature cycling from 0° C. to 600° C., and when exposed to molten lithium, molten lithium alloys, molten sulfur, or molten selenium.

[0040] The anode current collector may comprise any suitable material, such as, for example, stainless steel, copper, a copper alloy, carbon, graphite, or any combination of the foregoing. In a preferred embodiment, the anode current collector comprises stainless steel. The anode current collector may be inert upon exposure to molten lithium and / or molten lithium alloys.

[0041] The cathode current collector may comprise any suitable material, such as, for example, stainless steel, copper, a copper alloy, carbon, graphite, or a combination of any of the foregoing. In a preferred embodiment, the cathode current collector comprises stainless steel.

[0042] Electrochemical cell configurations are possible other than that illustrated in Figure 1. For example, the anode, solid electrolyte, and / or cathode may be in the form of parallel plates separating the anode from the cathode.

[0043] The anode can include lithium metal or a lithium alloy, for example, greater than 99.99 mole percent lithium, greater than 99.9 mole percent lithium, or greater than 99 mole percent lithium, where mole percent is based on the total number of moles of elements in the composition.

[0044] Suitable lithium alloys may have a melting temperature below 600° C., below 500° C., below 400° C., or below 300° C. Suitable lithium metal alloys may have a melting temperature within the range of, for example, 120° C. to 600° C., 120° C. to 500° C., 120° C. to 400° C., or 120° C. to 300° C. Examples of suitable lithium metal alloys include, for example, Li-Al, Li-Ag, Li-Si, and Li-Sn.

[0045] Under operating conditions, electrochemical cells provided by the present disclosure may be heated to a temperature above the melting temperature of the anode material such that lithium metal or lithium metal alloy melts during operation. For example, under operating conditions, the temperature of the cell may be below 600° C., below 500° C., below 400° C., or below 300° C., and above the melting point of lithium metal or lithium metal alloy.

[0046] The cathode may comprise sulfur or selenium, or a combination thereof. In some embodiments, the cathode comprises at least 50% sulfur or selenium, or a combination thereof, and in some embodiments, the cathode comprises at least 60%, 70%, 80%, 85%, 90%, 95%, 98%, 99%, 99.5%, 99.8%, 99.9% sulfur or selenium, or a combination thereof. In some embodiments, the cathode further comprises lithium.

[0047] The cathode may further include a carbon felt conductive additive in some embodiments. In some embodiments, sulfur or selenium (or mixture) and carbon are mixed in a molar ratio (m(S or Se):m(C)) of 3:1 to 20:1. In some embodiments, the molar ratio is at least 3:1, 4:1, 5:1, 6:1, 7:1, or 8:1. In some embodiments, the molar ratio is no higher than 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, or 20:1.

[0048] The solid electrolyte may include a material capable of conducting lithium ions. The solid electrolyte also maintains separation between the anode and the cathode during use. For example, the solid electrolyte may include a lithium ion conducting oxide, a lithium ion conducting phosphate, a lithium ion conducting sulfide, or any combination of the foregoing.

[0049] Examples of suitable lithium ion conducting oxides include garnet-type oxides, lithium superionic conductor (LISICON)-type oxides, perovskite-type oxides, and combinations of any of the foregoing.

[0050] The lithium ion conducting oxide is tantalum doped Li7La3Zr2O 12 The garnet-type oxide may include Li 7-x La3Zr 2-x Ta x O 12 where x can be, for example, from 0.1 to 1.0, from 0.2 to 0.9, from 0.3 to 0.8, or from 0.4 to 0.6.

[0051] Garnet-type oxides are Li 6.5 La3Zr 1.5 Ta 0.5 O 12 The garnet-type oxide may include Li 6.4 La3Zr 1.4 Ta 0.6 O 12- (also referred to herein as "LLZTO"). Garnet-type oxides include Li 6.6 La3Zr 1.6 Ta 0.4 O 12 The garnet-type oxide may include Li 6.5 La3Zr 1.5 Ta 0.5 O 12 may include.

[0052] Suitable lithium superionic conductor (LISICON) type oxides include, for example, Li 14 ZnGeO 16Suitable perovskite oxides include, for example, Li 3x La 2 / 3-x TiO3 and La (1 / 3)-x Li 3x NbO3, where x can be, for example, from 0.1 to 1.0, from 0.2 to 0.9, from 0.3 to 0.8, or from 0.4 to 0.7.

[0053] An example of a suitable lithium ion conducting phosphate is Li 1.4 Al 0.4 Ti 1.6 (PO4)3, LiZr2(PO4)3, LiSn2(PO4)3, and Li 1+x Al x Ge 2-x (PO4), where x can be, for example, 0.1 to 1.0, 0.2 to 0.9, 0.3 to 0.8, or 0.4 to 0.7.

[0054] Examples of suitable lithium ion conducting sulfides include Li2S-SiS2, Li2S-GeS2-P2S5, and combinations thereof.

[0055] The LLZTO solid electrolyte provided by the present disclosure may have a density of greater than 96%, greater than 97%, greater than 98%, or greater than 99%. For example, the LLZTO solid electrolyte may have a density of 96% to 99.9%, 97% to 99.9%, 98% to 99.9%, or 98% to 99%.

[0056] The LLZTO solid electrolyte provided by the present disclosure can be prepared using high pressure cold isostatic pressing and spray granulation.

[0057] The LLZTO solid electrolyte provided by the present disclosure can have a cross-sectional thickness of, for example, 0.1 cm to 0.6 cm, 0.15 cm to 0.5 cm, or 0.2 cm to 4 cm.

[0058] A sealant may be used to hold the cathode material in place during use. The sealant may be in the form of a paste or a gasket. It is desirable that the gasket material not degrade and maintain a viable seal under the conditions of use of the electrochemical cell. Suitable gasket materials do not significantly degrade after prolonged exposure of the anode and cathode materials to temperatures in the range of 200° C. to 600° C. or 200° C. to 300° C. Suitable gasket materials include elastomers such as silicones, perfluoroethers, polytetrafluoroethylene, and polyepoxides.

[0059] In some embodiments, the present disclosure provides an electrochemical cell comprising an anode comprising lithium metal or a lithium alloy, a cathode comprising sulfur or selenium, and a solid electrolyte positioned between the anode and the cathode, the solid electrolyte capable of conducting lithium ions. In some embodiments, the electrochemical cell has a capacity of at least 250 Wh kg -1 , 300Wh kg -1 , 400Wh kg -1 , 500Wh kg -1 , 600Wh kg -1 , 700Wh kg -1 , 800Wh kg -1 , 900Wh kg -1 , 1000Wh kg -1 , 1100Wh kg -1 , 1200Wh kg -1 , 1300Wh kg -1 , 1400Wh kg -1 , 1500Wh kg -1 , 1600Wh kg -1 , 1700Wh kg -1 , 1800Wh kg -1 , 1900Wh kg -1 , or 2000Wh kg -1 In some embodiments, the electrochemical cell achieves an energy density of at least 500 Wh L -1 , 600Wh L -1 , 700Wh L -1 , 800Wh L -1, 900Wh L -1 , 1000Wh L -1 , 1100Wh L -1 , 1200Wh L -1 , 1300Wh L -1 , 1400Wh L -1 , 1500Wh L -1 , 1600Wh L -1 , 1700Wh L -1 or 1800Wh L -1 This achieves an energy density of

[0060] The electrochemical cells provided by the present disclosure may be used in batteries and power modules that include more than one of the electrochemical cells. A power system may include more than one electrochemical cell and / or power module. The electrochemical cells and power modules may be used to store electrical energy and to discharge electrical energy to a power grid. Thus, aspects of the present invention include power systems and power grids that incorporate the electrochemical cells provided by the present disclosure. [example] [Example 1] Solid electrolyte-based molten lithium-sulfur and lithium-selenium batteries with high energy density

[0061] In this example, molten Li-S and Li-Se batteries with ceramic solid electrolyte tubes were fabricated and tested. A schematic diagram of the battery configuration is shown in FIG. 2a. It consists of a molten lithium metal anode, a molten S(Se) cathode, and an LLZTO ceramic tube electrolyte. The lithium metal anode was inside the LLZTO tube, and a stainless steel rod was inserted to act as the anode current collector. The S(Se) cathode with carbon felt conductive additive (having a mass ratio of m(S or Se):m(C)=9:1) was inserted into a stainless steel cylindrical container outside the LLZTO tube, which was physically and electronically separated from the lithium anode by the LLZTO tube. The stainless steel cylinder simultaneously acted as the cathode current collector. [method] Fabrication and characterization of garnet-type LLZTO tubes

[0062] Li2CO3 (Sinopharm Chemical Reagent Co., Ltd., 99.99%), La2O3 (Sinopharm Chemical Reagent Co., Ltd., 99.99%), ZrO2 (Aladdin, 99.99%) and Ta2O5 (Ourchem, 99.99%) powders were 6.5 La3Zr 0.5 Ta 1.5 O 12 The powders were mixed in a molar ratio of 0.1 to 0.25, ground in an agate mortar and pestle, and then heated at 900°C for 6 hours to decompose the metal salts. The resulting powders were ball milled for 12 hours before being pressed into U-tubes by cold isostatic pressing at 330 MPa for 120 seconds, and then annealed in air at 1140°C for 16 hours while the tubes were covered with the same mother powder. All heat treatments were performed in an alumina crucible (>99% Al2O3) covered with an alumina lid.

[0063] Archimedes water displacement method was used to measure the relative density of the LLZTO tubes. XRD (Bruker AXS D8 Advance with Da Vinci) was used to monitor the phase formation. The microstructure of the tubes was examined using a field emission SEM (Shimadzu SSX-550). A broadband dielectric spectrometer (NOVOCOOL) was used to perform impedance spectroscopy measurements (frequency range: 40 Hz-10 MHz, AC voltage: 10 mV, temperature range: 25 °C-300 °C). Assembly and electrochemical measurements of Li||LLZTO||S and Li||LLZTO||Se batteries

[0064] S (or Se) powder and carbon felt were first transferred to a stainless steel cell and heated in a box furnace (MTI) at 150°C (300°C) for 3 hours to uniformly disperse the molten S (or Se) in the carbon felt (with a mass ratio of m(S or Se):m(C) = 9:1). Next, lithium metal was placed in a garnet-type LLZTO tube and heated in a box furnace (MTI) at 240°C for 20 minutes to melt the lithium metal. The LLZTO tube containing the molten lithium was then transferred to a stainless steel cell with molten selenium at 240°C. A stainless steel rod with a diameter of 1 mm was inserted into the molten lithium as an anode current collector. After the cell was cooled to room temperature, silicone rubber was used to seal the cell with a stainless steel cap. The entire assembly process was carried out in a glove box under argon atmosphere.

[0065] The electrochemical performance of the Li||LLZTO||S and Li||LLZTO||Se cells was tested using a battery test system (LAND 2001 CT battery tester) at 240 °C and 300 °C in an argon-filled box furnace (MTI). The active surface area of ​​each cell was 3 cm2, as determined by the contact area between the LLZTO tube and the molten lithium. 2 The mass of active S in each battery is 10 Mg, and the mass of Se in each battery is 15 Mg. Calculation of energy density for molten Li-Se and Li-S batteries

[0066] Here, a realistic battery configuration is described to calculate its energy density. For the LLZTO solid electrolyte, a tube structure with a height of L cm, a wall thickness of 1.5 mm, and an inner diameter (D1) of 1 cm to 20 cm can be used. For the outer container (cathode current collector), this example uses a stainless steel case with a wall thickness of 2 mm, an inner diameter (D2) that is variable by D1 to ensure capacity matching with the anode and cathode. The cathode consists of 90 wt% S (or Se) fused to a conductive carbon felt. The conductive carbon required for melting S and Se occupies only 10% of the total electrode weight. Li metal occupies 90% of the internal volume of the LLZTO tube. S or Se occupies 45% of the total space between the LLZTO tube and the stainless steel container (see Figures 15 and 16).

[0067] 1) Assuming that D1 = 1 cm, the total internal volume of the LLZTO tube is V1 = 0.785 L cm 3 It is calculated as follows.

[0068] 2) The total volume and mass of lithium metal in the LLZTO tube is V Li =0.71L cm 3 , M Li =0.534*V Li =0.38L g.

[0069] 3) The total volume and mass of the active S between the LLZTO tube and the battery case is V S =0.37L cm 3 ,M S =2.36*V S =0.87L g.

[0070] 4) The total volume and mass of the LLZTO tube is V tube =0.54L cm 3 , M tube =5*V tube = 2.71 L g.

[0071] 5) The total volume between the LLZTO tube and the battery case is V2 = VS / 0.45=0.82L cm 3 It is calculated as follows.

[0072] The theoretical volumetric and gravimetric energy density is W V1 =2800*(V S +V Li ) / (V1+V tube +V2) = 1403 Wh L -1 W m1 =2600*(M S +M Li ) / (M S / 0.9+M tube +M Li )=800Wh kg -1 It is. Results and Analysis

[0073] The assembled Li||LLZTO||S and Li||LLZTO||Se batteries were tested at 240 °C and 300 °C (Fig. 6), which are above the melting points of both electrode materials. This battery design was feasible to achieve the high energy density typical of Li-S(Se) batteries. This is due to its structural simplicity, the significant reduction in the weight of inactive components, and the elimination of problems associated with conventional liquid electrolyte batteries. It was also observed that heating and insulation did not significantly affect the volumetric and gravimetric energy densities.

[0074] Based on the high capacity of both the cathode and anode materials, and utilizing a tightly packed battery configuration (Fig. 2b), our solid electrolyte batteries provide much higher energy densities than those achievable in conventional LIBs. The energy density of conventional LIBs is limited by the lithium storage capacity of their oxide cathodes and graphitic carbon anodes, as well as by the existing “sandwich” battery architectures, in which multiple layers of current collector / cathode / separator / anode / current collector are stacked or rolled together, resulting in a large fraction (~50%) of mass. Theoretical volumetric and gravimetric energy densities of molten Li||LLZTO||S and Li||LLZTO||S batteries were calculated based on all battery materials, including anode, cathode, solid electrolyte, and conductive additives (see Methods), and the results are plotted in Fig. 2c and d.

[0075] As the results show, the theoretical energy density of both batteries increases as the diameter of the LLZTO tube increases, generally reaching ~1850Wh kg for the Li||LLZTO||S battery when the diameter is larger than 6 cm (Fig. 2d). -1 and 1780Wh L -1 And for Li||LLZTO||Se battery, it is 920Wh kg -1 and 1570Wh L -1 As the operating temperature exceeds the melting points of lithium, sulfur, and selenium, both the anode and cathode materials are melted, facilitating rapid ion transport and low electrode-electrolyte interfacial impedance as a liquid-solid interface is formed rather than a solid-solid interface. The garnet-type ceramic electrolyte was selected for its stability towards molten lithium, which was verified through aging experiments (Figure 7). In addition, as the operating temperature increased, the ionic conductivity of the garnet-type solid electrolyte increased to a level that is competitive with rapid ion transport. At 240 °C, the ionic conductivity of the LLZTO electrolyte was measured to be 135 mS cm by electrochemical impedance spectroscopy (EIS) analysis. -1 (Figure 8) which is 0.7 mS cm at room temperature. -1At 300°C, the ionic conductivity was 190 mS cm -1 (Figure 9). In particular, the ionic conductivity of a typical organic liquid electrolyte at room temperature is about 10 mS cm -1 Take 1 molar LiPF6 salt in 1:1 ethylene carbonate-ethyl methyl carbonate electrolyte at 30°C as an example. The high ionic conductivity of the LLZTO tubes at elevated temperatures provides a solid basis for the high power capability of the battery.

[0076] In addition, the garnet-type electrolyte tube also acts as an insulating layer between the molten Li and the molten S / Se, which means that it is possible to completely prevent penetration and leakage. Based on our measurements (Archimedes method with ethanol), the relative density of the LLZTO tube is as high as 99%, indicating that the garnet-type solid electrolyte is dense. The surface and cross-sectional morphology measured by scanning electron microscope (SEM) of the tube was used to confirm the density of the structure (Figure 9). Nitrogen impermeability tests were also conducted (Figure 10) to verify the impermeability of the tube. Such high relative density and good impermeability enabled the LLZTO tube to prevent any leakage or crossover between the liquid electrodes (no shuttle effect, no lithium dendrite formation), ensuring the safety and reliability of the battery, and ensuring that the self-discharge rate is negligible.

[0077] To verify the electrochemical properties, a molten Li-S battery was assembled and tested at 240 °C. The voltage profile (Fig. 3a and Fig. 3c) shows that the discharge and charge plateaus are ~2.00 V and ~2.10 V, respectively. Fig. 3b shows the long cycling performance. During 50 cycles at a rate of 0.5 C, the performance of the Li||LLZTO||S battery is stable, with a capacity of about 1450 mAh g -1Figure 3c shows a gravimetric capacity of 1000 mAh g (91% utilization ratio of S). The stable coulombic efficiency can reach 99.99%, indicating that the side reactions of the electrode with the LLZTO tube or the crossover through the LLZTO tube are negligible. The energy efficiency is about 89%. Figure 3d shows the C-rate cycling performance from 0.5C to 3C at 240 °C. At 3C, the gravimetric capacity is about 750 mAh g -1 (47% usage ratio of S) was reached. In this experiment, high capacity can be maintained over 50 cycles in a molten Li-S battery. Further improvement can be realized by better sealing off the S vapor.

[0078] According to FIG. 2b, the S cathode has a higher lithium storage capacity and provides a higher energy density than is achievable with the Se cathode. However, the Se cathode has some advantages over the S cathode, such as a much higher electronic conductivity and a lower vapor pressure at elevated temperatures. Compared to sulfur, selenium has a much lower vapor pressure (FIG. 11), which means that the risk of large leaks is significantly reduced and therefore the sealing requirements and costs can be substantially reduced. For a clear comparison, a volatilization experiment was performed. Identical amounts (1 g) of selenium and sulfur in an open glass container were transferred to an oven under argon atmosphere at 300° C. and then the mass change was measured. These results (FIG. 12) show that in the case of selenium, almost no mass change occurred, while in the case of sulfur, the mass rapidly decreased to almost zero in 6 days. The lower vapor pressure of Se results in a substantially lower sealing requirement for molten Li-Se batteries.

[0079] The electrochemical results also verified the exceptional electrochemical performance of the Li||LLZTO||Se battery at 240 °C. The voltage profiles in Figures 4a and 4c show that the discharge and charge plateaus are ~2.04 V and ~2.12 V, respectively, which is consistent with the 1 C (30 mA cm) -2This means that the overpotential at a rate of 1 C is only 8 mV. Figure 4b shows the long cycling performance. During 300 cycles at a rate of 1 C, the performance of the Li||LLZTO||Se cell is very stable, which is about 650 mAh g -1 The results show a gravimetric capacity of 1000 mAh g (96% of the theoretical capacity of Se). The capacity fade was very small (~0.004% per cycle) throughout the test. The average coulombic efficiency was high at 99.99%, much higher than that of the battery using organic electrolyte (~98%). This indicates that the side reactions of the electrodes with LLZTO tubes and the crossover through the LLZTO tubes are negligible. The energy efficiency was stable at 87%. These results confirmed the feasibility and reliability of this battery design and further proved the stability of the LLZTO tubes. Figure 4d shows the cycling performance as a function of rate from 0.5C to 3C at 240 °C. Even at 3C, the gravimetric capacity was 560 mAh g -1 The voltage profiles at different rates are shown in Figure 4e. The main discharge flattened from 0.5C to 2C was almost the same at ~2.04V, and slightly decreased to 2.00V when the rate was increased to 3C. The battery was cycled 500 times at a rate of 3C, as shown in Figure 4f. The battery performance was very stable, with a capacity of about 500mAh g -1 The cells showed an average gravimetric capacity of 1000 mAh (74% usage ratio of Se). The average coulombic efficiency was 99.99% and the energy efficiency was 80%. The cells had high power capability at 240 °C. This can be attributed to the fast diffusion of lithium ions in the electrolyte, electrodes, and their interfaces. The fast lithium ion diffusion in the molten Se cathode can be explained based on the Li-Se phase diagram (Figure 7). As can be seen in the figure, molten lithium has a small but not negligible solubility in molten selenium at temperatures above 221 °C. This is because the Li-Se phase diagram shows that the Li:Se molar ratio in the cathode is <2, and the Li-saturated molten Se (~0.3 mol L−1) is the largest in the cathode. -1This means that a sufficient concentration of Li atoms is present in the cathode. If there is a sufficient concentration of Li atoms in the molten Se, they can act as carriers and improve the diffusion of lithium ions in the cathode during cycling.

[0080] In some specific applications, the discharge or charge process needs to be completed in a very short time, such as the fast charging mode of electric vehicles. This is difficult in organic electrolyte-based batteries because heat dispersion is an issue. In the current battery design, stable cycling at higher and higher rates can be easily achieved through adjustment of the operating temperature (Fig. 5a). When the operating temperature is increased to 300 °C, the lithium ion conductivity and charge transfer kinetics of the LLZTO tubes can be significantly increased compared to that at 240 °C (Fig. 8). The electrochemical performance of the Li-Se battery at 300 °C was investigated. As shown in Fig. 5b, when the operating temperature is increased from 240 °C to 300 °C, the gravimetric capacity increased to 300 mAh g at 4C. -1 From 640mAh g -1 The capacity increased significantly to 1000 mAh g−1, indicating a much better rate performance. Figure 5c shows that at high rate (4C), the battery remained stable in a cycling test involving 400 cycles. The average gravimetric capacity was about 640 mAh g−1. -1 The average coulombic efficiency remained high at 99.99%, and the energy efficiency was about 80. Figure 5d shows the C-rate cycling performance from 0.5 C to 10 C at 300 °C. The energy efficiency was about 180 mW cm -2 Equivalent to 10C (100mA cm -2 ) at high speeds, 400mAh g -1 A high gravimetric capacity was obtained (60% Se usage ratio). Figure 5e shows the cycling stability at 10 C. Even after 1000 cycles, the gravimetric capacity is still about 300 mAh g -1 (44% usage ratio of Se). The high power capability and stability of the battery system are confirmed by the fast and long cycling performance.

[0081] A freeze / thaw test was conducted from 240°C to 20°C during discharge / charge. The results can be seen in Figure 13. After freezing and thawing, regardless of the charge or discharge process, the battery worked normally without open or short circuit, and no variation in the cycle curve was observed. This means that no mechanical or electrochemical failure of the LLZTO tube occurred. The battery was resistant to the freeze / thaw cycle. The ability of the battery to recover after freezing is very important in practical applications. A self-discharge test was also conducted. Under the operating temperature of 300°C for 10 days between full charge and full discharge, the Li||LLZTO||Se battery still showed high coulombic efficiency and energy efficiency of 99.9% and 88%, respectively (see Figure 14). The results confirmed that no self-discharge occurred, indicating that the LLZTO solid electrolyte tube can well separate the anode from the cathode, and that there is no leakage or shuttle effect.

[0082] In summary, by employing a solid garnet-type LLZTO tube electrolyte, this example prepared molten Li-S and Li-Se batteries with high energy density and excellent electrochemical performance at 240 °C-300 °C. The assembled cells exhibited high coulombic efficiency (99.99%, no shuttle effect), high power capability (up to 180 mW cm), and excellent thermal conductivity (up to 1000 s). -2 ) and high energy efficiency (>80%).

[0083] From a cost perspective, the current energy cost of LLZTO tubes is approximately $30.1 kWh. -1 By using larger diameter LLZTO tubes, the energy cost can be reduced by $10kWh. -1 This is because the cost of liquid organic electrolytes and separators in LIBs (~$80 kWh -1 The theoretical complete electrode cost for Li-S and Li-Se batteries is $15 kWh, respectively. -1 and $41 kWh -1This is a very low estimate, and combined with the low cost of LLZTO tubes, the total price of molten Li-S and molten Li-Se batteries is estimated to be $100 kWh. -1 Overall, the low cost, high volumetric and gravitational energy density, and stable electrochemical performance of these solid electrolyte-based molten Li-S and Li-Se batteries make them promising candidates for concentrated large-scale energy storage applications.

[0084] Finally, it should be noted that there are alternative ways of implementing the embodiments disclosed herein. Accordingly, the present embodiments are to be considered as illustrative and not restrictive. Moreover, the claims are not to be limited to the details given herein, but are entitled to their full scope and equivalents.

Claims

1. an anode comprising molten lithium metal or a molten lithium alloy; a cathode comprising molten selenium; a solid electrolyte positioned between the anode and the cathode, the solid electrolyte being capable of conducting lithium ions; An electrochemical cell comprising: The solid electrolyte comprises a lithium ion conductive oxide, The lithium ion conductive oxide includes a garnet-type oxide, The garnet-type oxide is Li 7 -xLa 3 Zr 2 -xTaxO 12 where x is from 0.1 to 1.0; the solid electrolyte is in the form of a tube, the anode being disposed within the tube; The inner diameter of the tube is between 6 cm and 20 cm; The electrochemical cell is a rechargeable battery. Electrochemical battery.

2. The garnet-type oxide is Li 7 -xLa 3 Zr 2 -xTaxO 12 2. The electrochemical cell of claim 1 comprising:

3. The garnet-type oxide is Li 6.4 La 3 T 0.6 Zr 1.4 O 12 , Li 6.5 La 3 T 0.5 Zr 1.5 O 12 , or Li 6.6 La 3 T 0.4 Zr 1.6 O 12 10. The electrochemical cell of claim 1 comprising:

4. 4. The electrochemical cell of claim 1 further comprising a cathode current collector in electrical communication with the cathode.

5. 5. The electrochemical cell of claim 4 wherein said cathode current collector comprises stainless steel.

6. 5. The electrochemical cell of claim 4 further comprising an anode current collector in electrical communication with the anode.

7. 7. The electrochemical cell of claim 6, wherein said anode current collector comprises stainless steel.

8. 5. The electrochemical cell of claim 4, wherein the solid electrolyte has a relative density of from 95% to 99.9%.

9. 5. The electrochemical cell of claim 4 wherein said cathode current collector is in the form of a cylinder external to said tube, said cathode being disposed between said tube and said cylinder.

10. 5. The electrochemical cell of claim 4, further comprising a seal configured to retain the anode and the cathode.

11. 11. The electrochemical cell of claim 1, wherein the electrochemical cell is configured to operate at a temperature in the range of 120°C to 600°C.

12. 12. The electrochemical cell of claim 1, wherein the cathode further comprises a carbon conductive additive.

13. 13. The electrochemical cell of claim 12, wherein the selenium and carbon are mixed in a molar ratio (m(Se):m(C)) of 3:1 to 20:

1.

14. 14. A power module comprising one or more of the electrochemical cells according to any one of claims 1 to 13.

15. The power module of claim 14 further comprising a heat source configured to heat the one or more of the electrochemical cells.

Citation Information

Patent Citations

  • Composite negative-pole tube for battery

    CN106711465A

  • JP1974101829A

  • Solid electrolyte-based lithium-sulfur battery

    JP2014501436A

  • Electrode unit

    JP2015525450A

  • Molten lithium sulfur cell and manufacturing method thereof with solid electrolyte

    KR101803240B1